Frequency of cesarean section in pregnant women with risk factors for preeclampsia: prospective cohort study - Lejla Kamerić; Anis Cerovac; Mirzeta Rizvanović; Alen Kamerić; Mahira Jahić; Dubravko Habek (Clinical and Experimental Obstetrics & Gynecology, 2021)
Background: Preeclampsia is a disorder of pregnancy associated with new-onset hypertension after the 20th week of gestation. The aim of this study is to examine frequency of cesarean delivery in pregnant women with risk for developing preeclampsia compared with pregnant women with normal pregnancy. Methods: The prospective study included 240 pregnant women. The experimental group had 120 pregnant women with preeclampsia risk factors. The control group had 120 pregnant women with no pregnancy risk factors. The method of delivery completion was analyzed. Results: In the experimental group, 88 (73.3%) pregnant women completed delivery vaginally, by cesarean section in 32 (26.7%). In the control group of vaginally deliveries were 105 (87.5%), by cesarean section 15 (12.5%). The difference in the frequency of method of delivery between the experimental and control groups is not random (p = 0.009). The chance of completing a delivery by cesarean section 2.54 times is higher in the experimental than in the control group. In the control group, it was found that the RI of uterine arteries in women who delivered by cesarean section was statistically significantly higher than in vaginal delivery (p = 0.038). Conclusion: Cesarean section is the most commonly used surgical procedure to complete delivery in pregnant womens with risk factors for preeclampsia, which confirmed our study.